2020
DOI: 10.3390/cancers12010205
|View full text |Cite
|
Sign up to set email alerts
|

The Communication between the PI3K/AKT/mTOR Pathway and Y-Box Binding Protein-1 in Gynecological Cancer

Abstract: Studies of the mechanistic (mammalian) target of rapamycin inhibitors (mTOR) represent a step towards the targeted treatment of gynecological cancers. It has been shown that women with increased levels of mTOR signaling pathway targets have worse prognosis compared to women with normal mTOR levels. Yet, targeting mTOR alone has led to unsatisfactory outcomes in gynecological cancer. The aim of our review was therefore to provide an overview of the most recent clinical results and basic findings on the interpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 94 publications
1
20
0
Order By: Relevance
“…Beside PI3K and AKT inhibitors, drugs targeting the PI3K-Akt pathway include mTOR inhibitors, as mTOR kinase (Mechanistic Target Of Rapamycin Kinase) is part of the PI3K/Akt pathway. Trials investigating the role of different mTOR inhibitors in gynecological oncology are ongoing [45]. In vitro studies on vulvar cancer cell lines support the notion of application of mTOR inhibitors in VSCC treatment [10,46] These studies investigated Vistusertib (AZD2014) [10] belonging to the second generation of mTOR inhibitors, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Beside PI3K and AKT inhibitors, drugs targeting the PI3K-Akt pathway include mTOR inhibitors, as mTOR kinase (Mechanistic Target Of Rapamycin Kinase) is part of the PI3K/Akt pathway. Trials investigating the role of different mTOR inhibitors in gynecological oncology are ongoing [45]. In vitro studies on vulvar cancer cell lines support the notion of application of mTOR inhibitors in VSCC treatment [10,46] These studies investigated Vistusertib (AZD2014) [10] belonging to the second generation of mTOR inhibitors, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, patients with KMT2D mutations might benefit from aurora kinase inhibitors, as suggested by Williams et al [33], and recently shown in head, neck, and cervical cancer [42]. Nevertheless, the prognostic or therapeutic roles of the abnormalities in this pathway in VSCC are yet to be elucidated [43].…”
Section: Discussionmentioning
confidence: 97%
“…YBX3 and YBX1could convey profound anti- and pro-oncogenic effects on AKT pathway dependent cell transformation ( 38 ). In gynecological cancer, YBX1 was shown to be an important player impacting AKT and the downstream genes such as EGFR, Snail, or E-cadherin ( 39 ). Thus, these findings suggested that YBX3 and YBX superfamily were closely associated with PI3K/AKT pathway.…”
Section: Discussionmentioning
confidence: 99%